The patient journey and burden of disease in progressive pulmonary fibrosis in Japan: a cross-sectional survey - Kaneko, Yuko; Waseda, Yuko; Yasuoka, Hidekata; Okazaki, Masateru; Nagata, Shoko; Iwasaki, Ryoko; Small, Mark; Ishii, Haruyuki (Frontiers in Medicine, 2025)
BackgroundFor patients with interstitial lung diseases (ILDs) other than idiopathic pulmonary fibrosis (IPF) with a progressive pulmonary fibrosis (PPF) phenotype, current knowledge of patient experience and symptom burden is limited. This study aimed to describe the patient journey for patients with PPF and IPF in a real-world setting in Japan.MethodsData were analyzed from the Adelphi Real World PPF-ILD Disease Specific Programme™, a cross-sectional survey with elements of retrospective data collection of pulmonologists and rheumatologists in Japan from April to October 2022. Participants provided data for up to 12 consecutive patients with physician-confirmed ILD with a progressive phenotype. Analyses were descriptive, except Kappa (κ) statistic was used to measure the alignment between physician- and patient-reported symptom burden in the 4 weeks prior to survey date (poor agreement: κ =<0.00; slight 0.00–0.20; fair 0.21–0.40; moderate 0.41–0.60; substantial 0.61–0.80; almost perfect 1.00).ResultsA total of 63 physicians (43 pulmonologists and 20 rheumatologists) provided data on 382 patients (312 with PPF and 70 with IPF). These patients were also asked to complete a voluntary survey on their experience and symptoms. Mean time from first symptom to consultation was 14.1 months for IPF, 8.0 months for non-connective tissue disease (CTD)-associated ILDs, and 10.7 months for CTD-ILDs. Mean times from consultation to diagnosis were 7.1, 4.8, and 3.6 months, respectively. Perception of symptoms differed between physicians and patients with alignment ranging from poor (dysphagia, κ = –0.0296, p = 0.6217) to substantial (weight loss, κ = 0.6174, p = 0.001). Health-related quality of life (HRQoL) was consistently impaired in patients overall, but too few patients completed HRQoL instruments to compare IPF with other forms of ILD.ConclusionsThis real-world study expands our understanding of the patient journey for patients with PPF and IPF in Japan. Greater communication between patients and physicians is needed to shorten diagnostic delays and target treatment strategies to improve patient experience and overall outcomes.